Labor regulations and European private equity - National Bureau of Economic Research, Cambridge; Bozkaya, Ant; Kerr, William R. (Cambridge, MA, 2009)
"European nations substitute between employment protection regulations and labor market expenditures (e.g., unemployment insurance benefits) for providing worker insurance. Employment regulations more directly tax firms making frequent labor adjustments than other labor insurance mechanisms. Venture capital and private equity investors are especially sensitive to these labor adjustment costs. Nations favoring labor expenditures as the mechanism for providing worker insurance developed stronger private equity markets in high volatility sectors over 1990-2004. These patterns are further evident in US investments into Europe.In this context, policy mechanisms are more important than the overall insurance level provided."